Research of thermal processes for the continuous casting of steel - Velicka, Marek (Materiali in tehnologije, 2013)
The article deals with the determination of the basic indicators of heat transfer in the continuous casting of steel, which can be described as an unsteady process with complicated boundary conditions for the solution. An analytical solution of this problem is practically impossible and, therefore, mathematical modelling is applied with a certain simplification of the real conditions and with a description of those criteria that influence the most the process of solidification and cooling. Using a simulation program and the knowledge of input parameters, it was possible to predict the distribution of the thermal field of a continuously cast blank in the course of its casting. Simulations also allowed us to deal with the issues of the inner structure, surface quality, mechanical properties of a continuously cast blank, metallurgical length, change in the thickness of a strand shell and overheating of steel. Some results obtained with numerical simulations are documented for concrete examples.
Keywords: kontinuirno ulivanje; continuous casting; modeliranje; modelling; heat transfer; prenos toplote; shell; skorja; kokila; mould